The eastern cape automotive cluster: a key sector for regional economic growth and development - Gideon Horn (European Regional Science Association (ERSA), 2002)
In terms of the human development index, the Eastern Cape Province is the second poorest of the nine provinces in South Africa. The Province suffers from high levels of unemployment and illiteracy, low levels of international competitiveness and productivity, as well as low levels of resource beneficiation. The manufacturing sector is currently the only growth sector in the Eastern Cape Province, with the motor cluster comprising the majority of manufacturing activities in the Province. The Eastern Cape is in fact regarded as the 'Mecca' of the country's motor industry. Unfortunately, the following factors are constantly impacting either positively or negatively on the South African motor industry: a) The replacement of the General Agreement on Tariffs and Trade (GATT) by the World Trade Organisation (WTO) and the General Agreement on Trade in Services (GATS), have significant effects as far as import tariffs and export subsidies are concerned. The South African motor industry has become a global competitor and is now subjected to all the international rules of the game. b) The phasing out of the General Export Incentive Scheme (GEIS) in due course will have a major impact on especially marginal motor manufacturers. c) Cost factors such as the depreciating Rand, the international oil price, the high cost of labour in South Africa and the country's so-called inflexible labour laws, all impact on the motor industry. The objectives of this research paper are to: a) Explain how the motor industry in the Province, despite the factors impacting on it and the changing conditions in which it operates, is still the major sector of economic growth and employment. b) Outline the new rules and regulations as embodied in the WTO and GATS, and to investigate the specific implications which these new rules and regulations have for the motor industry. c) Determine whether firms in the South African motor industry who are successful in obtaining export contacts, are internationally competitive in the production of motor cars itself, or components only, or both. d) Investigate how firms in the motor industry need to adjust to international trends and rules in order to become internationally more competitive.
Keywords: 330